Nutritional Evaluation of Sweet Orange (Citrus sinensis) Fruit Peel as a Feed Resource in Broiler Production - Agu, P.N.; Oluremi, O.I.A.; Tuleun, C.D. (International Journal of Poultry Science, 2010)
A study was conducted with broiler chicks to evaluate the nutritional potential of Sweet orange fruit (Citrus sinensis) peel as a feed resource. Sweet orange peels were sun dried, milled and used as a dietary substitute for maize. Six experimental diets coded as M100P0, M90P10, M80P20, M70P30, M60P40 and M50P50 were compounded such that Sweet Orange Peel Meal (SOPM) substituted maize at levels of 0, 10, 20, 30, 40 and 50%, respectively in broiler starter and finisher diets. One hundred and eighty (180) day-old Anak titan chicks were randomly divided into six groups and one of each was allotted to a diet of three replicates. The birds which were raised in deep litter pens for sixty-three days were fed ad libitum and had access to fresh cool drinking water daily. Performance data: feed intake, water consumption, body weight, Body Weight Gain (BWG), Feed Conversion Ratio (FCR) were collected during the feeding trial and carcass evaluation was done at the termination of the trial. In both starter and finisher phases, the diets had no effect (p>0.05) on feed intake, water consumption, body BWG and FCR but had significant effect (p0.05) on kidney, liver, heart, spleen, gall bladder and lung but had significant effect (p